Chapter «Un arancio in gennaio». La Vita del beato Giovanni Colombini di Feo Belcari da racconto agiografico a testo di lingua - De Gregorio, Mario (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2020)
Composed between 1448 and 1449, the Vita del beato Giovanni Colombini by Feo Belcari was printed for the first time in 1477 and was destined to growing publishing success over the following centuries both as an independent text and in miscellany dedicated to the blessed. It will be the third edition of the Accademia della Crusca Vocabolario, published in 1691, to increase its affirmation by admitting the entire poetic and prose work of Belcari among the privileged references for the Tuscan vernacular and the Italian language. A recognition that will lead to a Veronese edition of the work in 1817, edited by authoritative scholars of Italian humanistic literature, which will condition many reprints of the work during the first half of the nineteenth century and which will persist even later, when it will be included in series very different, between religious and linguistic / literary interests.